Pengaruh Rasio Likuiditas dan Solvabilitas Terhadap Rasio Profitabilitas Pada PT Solusi Bangun Indonesia Tbk Periode 2011-2020 - Akhmad Akbar (Jurnal EMT KITA, 2022)
This study aims to determine the effect of the Liquidity Ratio which is proxied by the Current Ratio (CR) and the Solvency Ratio which is proxied by the Debt to Assets Ratio (DAR) on the Profitability Ratio which is proxied by the Return on Assets (ROA) at PT Solusi Bangun Indonesia Tbk. period 2011-2020. The research method used is quantitative research by looking for causal associative relationships and using classical assumption tests, hypothesis testing (t test and F test), coefficient of determination test, using SPSS version 25 program. The results of the study are Current Ratio partially significant effect and is positively related to Return on Assets. Judging from the results of the partial test (t test), the CR variable with a value of tcount > ttable is 3,448 > 2,365 and a significant value of 0.011 < 0.05. Debt to Asset Ratio partially has a significant and negative effect on Return on Assets. Judging from the partial test (t test), the DAR variable with a value of tcount > ttable is -4.229 > 2.365 and a significant value of 0.004 <0.05. Current Ratio and Debt to Assets Ratio simultaneously have a significant effect on Return on Assets. Judging from the simultaneous test (F test), Fcount > Ftable, which is 38.058 > 4.74 and a significant value of 0.000 <0.05. Based on the coefficient of determination test, the R-Square of 0.916 means that the contribution of the Current Ratio and Debt to Asset Ratio variables to Return on Assets is 91.6% while the remaining 8.4% is influenced by other variables not used in this study.